Improvement in aerobic capacity after an exercise program in sporadic inclusion body myositis - Johnson, L.; Collier, K.; Edwards, D.; Philippe, D.; Eastwood, Peter; Walters, S.; Thickbroom, G.; Mastaglia, F. (2009)
OBJECTIVES:: The study aimed to investigate the effects of a combined functional and aerobic exercise program on aerobic capacity, muscle strength, and functional mobility in a group of patients with sporadic inclusion body myositis (IBM). METHODS:: Aerobic capacity, muscle strength, and functional capacity assessments were conducted on 7 participants with sporadic IBM before and after a 12-week exercise program, which included resistance exercises and aerobic stationary cycling 3 times per week on alternative days. RESULTS:: Aerobic capacity of the group increased significantly by 38%, and significant strength improvements were observed in 4 of the muscle groups tested (P < 0.05). The exercise program was well tolerated, and there was no significant change in the serum creatine kinase level after the exercise period. CONCLUSIONS:: An aerobic exercise program can be safely tolerated by patients with sporadic IBM and can improve aerobic capacity and muscle strength when combined with resistance training. These findings indicate that aerobic and functional muscle strengthening exercise should be considered in the management of patients with IBM. Copyright © 2009 by Lippincott Williams & Wilkins.